Pengaruh Konten TikTok terhadap Minat Beli Kuliner melalui Kepuasan dalam Perspektif Bisnis Islam - Wila Bayu Femmya Angel; Femei Purnamasari; Agus Kurniawan (ARBITRASE: Journal of Economics and Accounting, 2025)
This study seeks to examine the impact of TikTok content on consumers' purchasing intentions for culinary products in Bandar Lampung, with customer satisfaction acting as a mediating variable within the context of Islamic business ethics. The study examines the TikTok culinary account @alejenes, recognized for its significant interaction with local audiences. Utilizing a quantitative approach and an explanatory study design, data were gathered from 100 active followers via an online survey and analyzed employing the SEM-PLS technique. The results show that tiktok content has a significant effect on satisfaction (coefficient = 0.500; t = 7.090; p < 0.001), and satisfaction significantly affects purchase intention (coefficient = 0.487; t = 5.044; p < 0.001). However, the direct effect of tiktok content on purchase intention is not significant (coefficient = 0.069; p = 0.500), which indicates full mediation by the satisfaction variable (indirect effect = 0.244; t = 4.005; p < 0.001). The R-square value for satisfaction is 0.250 and for purchase intention is 0.275, indicating the contribution of the model in explaining the variance of the two variables. From an Islamic business standpoint, content that adheres to ethical ideals and Sharia standards fosters consumer trust and loyalty. This research emphasizes the significance of incorporating ethical and innovative digital marketing methods via social media to effectively enhance culinary purchasing interest in the digital age.